10. Somatosensory Evoked Potentials as predictors of evolution toward brain death in comatose patients after acquired brain injury. Issue 12 (December 2016) - Scarpino, M.; Lanzo, G.; Carrai, R.; Lolli, F.; Migliaccio, M.L.; Spalletti, M.; Cozzolino, M.; Peris, A.; Amantini, A.; Grippo, A.
Abstract : We assessed whether Somatosensory Evoked Potentials (SEPs), recorded within 24 h after ICU admission, are reliable predictors of brain death (BD) in comatose patients with acquired brain injury (ABI) of several aetiologies. SEPs were classified as Absent (A), Pathological (P), and Normal (N). Taking into consideration responses in both hemispheres, six SEP patterns were defined: NN, NP, PP, AN, AP, and AA. The final endpoint was BD. Of the 203 patients, 70 (34%) evolved toward BD. Using survival analysis, the comparison of survival curves indicated that the most powerful aggregation of SEP patterns resulted in the following: grade I (NN-NP-PP-NA) and grade II (AP-AA). This aggregation predicted BD with a sensitivity of 75.7% (CI 64–84) and a specificity of 76.6% (CI 68–83) in overall patients, and with a sensitivity of 75.0% (CI 63–84) and a specificity of 84.9% (CI 75–90) in all patients excluding cardiac arrest. It is worth including SEPs, in association with other instrumental and clinical signs, in prognostic scores of BD. The early identification of patients that would probably evolve toward BD could help physicians to identify potential organ donors and to optimise their diagnostic-therapeutic work-up.